2010
DOI: 10.1002/dvdy.22338
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes expressed by zebrafish oligodendrocytes using a differential microarray screen

Abstract: Myelination of central nervous system axons requires that oligodendrocytes extend multiple membrane processes that specifically recognize and wrap axons, which is followed by expression of proteins necessary for formation of myelin sheaths. To identify new genes that might be important for myelination, we used microarrays to analyze the expression profiles of cells sorted from transgenic zebrafish embryos and larvae under conditions that permitted or blocked oligodendrocyte development. Here, we describe eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
3
25
0
1
Order By: Relevance
“…The location and shape of these cells was similar to SOX10-positive oligodendrocyte; the myelin-forming cells (36,37). These results suggest that MCT8 transports THs from the blood vessels into oligodendrocytes and neurons, and regulates myelination and neuron development.…”
Section: I J L M An O)mentioning
confidence: 61%
See 1 more Smart Citation
“…The location and shape of these cells was similar to SOX10-positive oligodendrocyte; the myelin-forming cells (36,37). These results suggest that MCT8 transports THs from the blood vessels into oligodendrocytes and neurons, and regulates myelination and neuron development.…”
Section: I J L M An O)mentioning
confidence: 61%
“…In addition, mct8 expression was observed in oval cell bodies with short projections that did not express both HUC and GFAP markers. Because the structure and the location of these cells are similar to sox10 expressing cells (36,37), they are likely to be oligodendrocytes. Similarly, in mammals, mct8 mRNA and protein were present in oligodendroglial cells derived from mice (50).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we use zebrafish, which have recently become established as a powerful model for the study of glial cells and myelinated axons (Brosamle and Halpern, 2002;Buckley et al, 2010;Kazakova et al, 2006;Kirby et al, 2006;Li et al, 2007;Lyons et al, 2009;Monk et al, 2009;Pogoda et al, 2006;Takada and Appel, 2010), to study the role that axons play in regulating CNS myelination in vivo. As is the case in mammals, we show that single oligodendrocytes in zebrafish myelinate either a small number of large caliber axons or a larger number of smaller axons.…”
Section: Introductionmentioning
confidence: 99%
“…Neurospheres formed mainly from the proliferation of GFAP + radial glia cells that served as neural progenitors able to self-renew and differentiate after withdrawal of growth factors for three consecutive culture passages ( Figure S3E, arrowhead; data not shown). After 4 days in vitro in the absence of growth factors (Div4d), zebrafish neurospheres differentiated into all neural cell types: astrocytelike cells (GFAP + ) (Nielsen and Jørgensen, 2003), oligodendrocytes (Sox-10 + ) (Takada and Appel, 2010), and mature neurons (a-tubulin + ) (Ulrich et al, 2011) and expressed gene markers of several postmitotic neural cells (Figures S3F, arrowheads, and S3G). qRT-PCR analysis indicated that, during the course of neurosphere differentiation, dicer mRNA levels progressively declined, while miR-107 expression increased ( Figures 5A and 5B).…”
Section: Loss Of Mir-107 Function Promotes Hindbrain Neurogenesismentioning
confidence: 96%